2018
DOI: 10.25159/2520-5293/3858
|View full text |Cite
|
Sign up to set email alerts
|

Caring for mental health care users with profound intellectual disabilities: Approaches and opportunities

Abstract: Mental healthcare users with profound intellectual disabilities are among the most disadvantaged groups in society. They experience numerous challenges which include limitations in intellectual functioning and adaptive behaviour. These limitations present challenges in their care, especially in cases where student nurses are not well prepared to meet these special needs. The purpose of this study was to provide insight into approaches and opportunities related to the care of mental healthcare users with profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Other studies (Ally et al, 2018;Grossman & Magana, 2016;Smith & Anderson, 2014) have indicated that transition planning should be introduced at an early age so that alterations can be made where possible, and Ally et al (2018) adds that this process should be started early from the age of 12-16 years. Malapela et al (2017) recommend that an integrated team of healthcare workers should be actively involved in the transition planning of adolescents with intellectual disabilities. Stakeholder institutions including schools, government and the civil society have key roles to play in strategic planning for transitioning children with intellectual disability from schools in with the view to improve their welfare and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies (Ally et al, 2018;Grossman & Magana, 2016;Smith & Anderson, 2014) have indicated that transition planning should be introduced at an early age so that alterations can be made where possible, and Ally et al (2018) adds that this process should be started early from the age of 12-16 years. Malapela et al (2017) recommend that an integrated team of healthcare workers should be actively involved in the transition planning of adolescents with intellectual disabilities. Stakeholder institutions including schools, government and the civil society have key roles to play in strategic planning for transitioning children with intellectual disability from schools in with the view to improve their welfare and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Societies expect that successful completion of school among adolescents without disabilities would lead either to further education or employment because of availability of public and private opportunities for further studies, vocational training and employment (Henninger & Taylor, 2014; Pandey & Agrawal, 2013). These criteria, however, elude adolescents with intellectual disabilities (IDs) depending on the level of disability (Malapela, Mfidi, & Sibanda, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition also includes many adjustments that have to occur in life. Such events include leaving parents to boarding school, leaving home after parental death to an orphanage and all other life events that may render one to transit from one area to another [8]. Chick and Meleis [9] summarises transition by defining it as 'a passage or movement from one state, condition or place to another' (p239).…”
Section: Transition As a Conceptmentioning
confidence: 99%
“…Transition Possibilities for Adolescents with Intellectual Disabilities into Adulthood DOI: http://dx.doi.org /10.5772/intechopen.89174 However, in most countries, especially developing countries, they do not have structures in place to assist them achieve this milestone [8]. Most often, there are no programmes and policies suited for addressing their needs.…”
Section: Transition Of Adolescents With Intellectual Disabilitiesmentioning
confidence: 99%